2016
DOI: 10.2344/15-00016.1
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Midazolam Sedation in a Pediatric Emergency Dental Clinic

Abstract: The purpose of this study was to compare the effectiveness and recovery times of 0.3 and 0.5 mg/kg intranasal midazolam (INM) administered with a mucosal atomizer device (MAD) in a pediatric emergency dental hospital clinic. One hundred eighteen children aged from 4 to 6 years were randomly administered either 0.3 or 0.5 mg/kg INM via an MAD in a triple-blinded randomized controlled trial. Sedation was achieved to some degree in 100% of the sample. The pulse rate and oxygen saturation were within the normal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This reveals that higher dose of intranasal midazolam offers greater probability of children to be calm (sedation scale score 3) during separation from their parents and face mask induction compared to lower dose with no adverse effects. This is similar to studies by Baldwa 12 and Peerbay et al 14 where higher doses were found more effective and in contrast to others showing equivalent sedation levels during parental separation, induction and intravenous cannulation with both the doses, probably due to lesser accurate drug delivery of higher dose. 6,15,16 A study by Al-Rakaf H et al 10 found all three doses (0.3 mgkg −1 , 0.4 mgkg −1 and 0.5mgkg −1 ) of intranasal midazolam effective in modifying the behavior of the uncooperative child to accept dental treatment.…”
Section: Discussionsupporting
confidence: 90%
“…This reveals that higher dose of intranasal midazolam offers greater probability of children to be calm (sedation scale score 3) during separation from their parents and face mask induction compared to lower dose with no adverse effects. This is similar to studies by Baldwa 12 and Peerbay et al 14 where higher doses were found more effective and in contrast to others showing equivalent sedation levels during parental separation, induction and intravenous cannulation with both the doses, probably due to lesser accurate drug delivery of higher dose. 6,15,16 A study by Al-Rakaf H et al 10 found all three doses (0.3 mgkg −1 , 0.4 mgkg −1 and 0.5mgkg −1 ) of intranasal midazolam effective in modifying the behavior of the uncooperative child to accept dental treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The reported drowsiness and relaxation responses in this trial demonstrate that sedation via intranasal dosing with remimazolam is feasible, even with a nonoptimized formulation. Onset times were faster than those typically reported for midazolam, which is used intranasally with some success, e.g., for imaging or in dental practices [11][12][13][14][15]. A limitation of the current trial design was the use of non-optimized IV formulation, resulting in the need to apply large volumes of either solution or powder in order to achieve clinical effects.…”
Section: Discussionmentioning
confidence: 93%
“…The clinical need for intranasal sedation is given by fear of injection, particularly in younger patients. Therefore, to be a clinically useful alternative, intranasal treatment must be demonstrably at least as tolerable as intravenous injection [14]; something which the current intravenous formulation does not seem to offer when administered intranasally: it causes considerable local discomfort (thus negating the purpose of the intranasal route).…”
Section: Discussionmentioning
confidence: 99%
“…[4] It is useful in those patients whose anxiety levels are more and who are unlikely to cooperate during minor oral surgical procedures, and can be induced by various routes of administration such as inhalation, intranasal (IN) spray, IV, oral, and intramuscular routes. [5] In this study, patients were chosen for IN and IV routes of midazolam administration.…”
Section: Discussionmentioning
confidence: 99%